2020
DOI: 10.1007/s43440-020-00142-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metformin on HIF-1 pathway in multiple myeloma

Kinga A. Kocemba-Pilarczyk,
Sonia Trojan,
Barbara Ostrowska
et al.

Abstract: Background Multiple myeloma (MM) is defined as plasma cells malignancy, developing in the bone marrow. At the beginning of the disease, the malignant plasma cells are dependent on bone marrow microenvironment, providing growth and survival factors. Importantly, the recent studies pointed hypoxia as an important factor promoting progression of MM. In particular, hypoxia-triggered HIF-1 signaling was shown to promote chemoresistance, angiogenesis, invasiveness and induction of immature phenotype, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Recent studies showed that CD39 expression was not induced by IFN-γ [ 59 , 60 ] whereas it can be induced under hypoxic conditions [ 61 , 62 ]. ETCI inhibitors have already been reported to interfere with HIF stabilization such as IACS [ 15 , 63 ] and metformin [ 64 , 65 , 66 ]. EVT-701 was also developed from a screening campaign to characterize HIF-1α inhibitors [ 22 ]; therefore, we propose an impairment of hypoxic signaling by interfering with HIF-1α stabilization as the mechanism by which EVT-701 decreases CD39 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that CD39 expression was not induced by IFN-γ [ 59 , 60 ] whereas it can be induced under hypoxic conditions [ 61 , 62 ]. ETCI inhibitors have already been reported to interfere with HIF stabilization such as IACS [ 15 , 63 ] and metformin [ 64 , 65 , 66 ]. EVT-701 was also developed from a screening campaign to characterize HIF-1α inhibitors [ 22 ]; therefore, we propose an impairment of hypoxic signaling by interfering with HIF-1α stabilization as the mechanism by which EVT-701 decreases CD39 expression.…”
Section: Discussionmentioning
confidence: 99%
“…HIF1-α directly binds to HREs on the proximal miR-210 promoter [ 152 , 153 ]. Furthermore, hypoxia-induced miR-210 increases the mRNA levels of VLA4 , CXCR4 , IL6 , and TGFB in MM cells [ 180 ]. miR-210 expression is significantly correlated with that of the hypoxia-inducible genes in myeloma cells [ 179 ].…”
Section: Hypoxiamentioning
confidence: 99%
“…Western Blot analysis was performed as described previously [48]. Primary antibodies used were as follows: anti-HIF-1 alpha antibody (Cell Signaling Technology, Danvers, MA, USA, cat.…”
Section: Western Blotmentioning
confidence: 99%